Green Accounting Practices in Bali’s Hospitality Industry: A Strategic Approach to Sustainable Hotel Management - Ayu Dwi Yulianthi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The hospitality industry in Bali faces increasing pressure to balance economic growth with environmental sustainability due to its significant ecological impact from resource consumption and waste generation. This study aims to examine the implementation of green accounting practices in ten major hotels in Bali, focusing on environmental protection, waste management, eco-friendly purchasing, and energy conservation. A qualitative approach was employed, utilizing semi-structured interviews with hotel managers and direct field observations to gather data. The findings reveal that most hotels demonstrate good to excellent green accounting practices, including energy-efficient technologies, organic waste composting, local product sourcing, and community-based conservation initiatives. Notable performers include St. Regis Bali Resort and Conrad Bali, while others, such as Grand Hyatt Bali, show moderate adoption. These practices enhance operational efficiency and corporate reputation. The study concludes that green accounting supports sustainable tourism in Bali, though standardization of environmental reporting is needed for greater transparency. Recommendations include developing standardized frameworks and investing in local recycling infrastructure to strengthen sustainability efforts, ensuring Bali remains a leading environmentally responsible tourism destination.